Tracing the Influence of Clement of Alexandria on the Acts of Peter and the Twelve Apostles (NHC VI,1) - Schiesaro, GianMarco (Apocrypha, 2023)
Abstract The Acts of Peter and the Twelve Apostles (NHC VI,1), despite its brevity, is a remarkably diverse document, drawing from an array of sources and themes, and displaying a broad spectrum of literary genres and Christological interpretations. The pearl’s theological-literary motif potentially finds its roots in a Syriac context, whereas the final compilation of the work is seemingly associated with the region of Alexandria. A comparative analysis with Clement of Alexandria’s Paidagōgos highlights striking similarities between the two texts, particularly in the depiction of the apostolic ministry, bestowed by Jesus to the apostles, to serve as “healers of bodies and souls” of the faithful. Additional evidence in Clement’s other works indicates parallels between the Christian’s journey towards gnosis and the allegorical-spiritual voyage undertaken by the apostles in the Acts. A potential correlation can be identified between the angelological and ascetic motifs present in Clement’s works and those in the Acts. Further exploration of vernacular themes from Alexandria to Upper Egypt and Nubia reveals considerable influences from popular magic and Greco-Coptic piety. The final version of the work seems to weave Clementine theological motifs into a popular framework, merging these foundational themes with the broader cultural milieu. Abstract Les Actes de Pierre et des Douze Apôtres (NHC VI,1), malgré leur brièveté, sont un document remarquablement divers, puisant dans un éventail de sources et de thèmes, et présentant un large spectre de genres littéraires et d’interprétations christologiques. Le motif théologico- littéraire de la perle trouve potentiellement ses racines dans un contexte syriaque, tandis que la compilation finale de l’oeuvre est apparemment associée à la région d’Alexandrie. Une analyse comparative avec le Pédagogue de Clément d’Alexandrie met en évidence des similitudes frappantes entre les deux textes, en particulier dans la description du ministère apostolique, conféré par Jésus aux apôtres, pour servir de “guérisseurs des corps et des âmes” des fidèles. Des éléments provenant d’autres oeuvres de Clément indiquent des parallèles entre le voyage du chrétien vers la gnose et le voyage allégorique et spirituel entrepris par les apôtres dans les Actes. Un lien potentiel peut être identifié entre les motifs angéliques et ascétiques dans les oeuvres de Clément et ceux des Actes. Une exploration plus poussée des thèmes vernaculaires depuis Alexandrie jusqu’à la Haute-Égypte et la Nubie révèle des influences considérables de la magie populaire et de la piété gréco-copte. La version finale de l’ouvrage semble tisser les motifs théologiques clémentins dans un cadre populaire, fusionnant ces thèmes fondateurs avec le milieu culturel plus large.